The Interrelation Between Hardiness and Prognostic Potential of Students of Higher Education Institutions - Bazhdanova, Yuliya V. (2020)
The paper presents the results of an empirical study of specific features and the relationship between hardiness of students and prognostic potential of their personality. The methods of research comprised: theoretical analysis, empirical research (testing), qualitative analysis of the obtained data, mathematical and statistical data processing (SPSS Statistics, Excel). It has been found that students with a high level of prognostic potential development are distinguished by pronounced personality traits typical of hardy people. The authors have proved in the paper that the prognostic potential of students is a holistic system of personality resources, which is based on specific features of thinking and building a secondary image. There are criteria and development levels of the prognostic potential among students: an internal criterion (features of thinking and building secondary images) and an external criterion (the effectiveness of forecasting activities, the conformity of the stages of prognostic activity with the reference model). The prognostic potential is interconnected with personal and professional characteristics of students (features of the intellectual, communicative, emotional-volitional and motivation spheres). There are significant differences between students with different levels of development of prognostic potential according to the main personal and professional features. The correlation analysis of the data gave the following interrelations: there is a direct interrelationship between the level of development of prognostic potential and emotional stability of students; between the level of development of prognostic potential and such motives for studying at a university as professional and educational-cognitive motives; between the level of development of prognostic potential and the features of self-regulation. On the basis of the results of an empirical study, the authors designed a program for the prognostic potential development of students which includes active teaching methods, lectures, and trainings.